Determinant Factors Influencing Organic Food Purchase Intention (Journal of Management, 2022)
Consumers have become highly concerned about their enduring health and moulding behaviour towards health benefits purchases. With regard to this, the paper aims to examine the determining factors that influence the purchase intention of organic food in Biratnagar. Among different exploratory factors, this paper aims to study the impact of trust, health consciousness and knowledge on the purchase intention of organic food. A self-administered questionnaire was sent on a random basis and 170 responses were recorded. To investigate the correlation among the variables Pearson Correlation was used and Multiple regression to find the impact of different factors on the purchase intention of organic food. The research findings reported that knowledge was the key determinant factor and showed a positive significant impact on purchase intention. Trust and health consciousness didn’t significantly impact organic food purchases. The article recommends that government and policymakers give immense attention towards organic farming and provide necessary awareness to encourage the purchase of organic food.